2013
DOI: 10.1002/ps.3487
|View full text |Cite
|
Sign up to set email alerts
|

Influence of soil environments on nematicidal activity of fluensulfone against Meloidogyne javanica

Abstract: Fluensulfone nematicidal activity and movement were affected by organic matter and clay content, probably via adsorption. Enhanced biodegradation or cross-biodegradation of fluensulfone by other compounds was not observed. Soil environment should be considered to obtain effective nematode control efficacy with a given compound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
2
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 25 publications
(37 reference statements)
0
41
2
1
Order By: Relevance
“…In experiment 1, all chemical nematicides reduced root galling on tomato, whereas in experiment 2, only fluensulfone showed a trend towards nematode suppression. Although studies have shown that differences in the soil environment, such as organic matter and clay content, can alter nematicidal activity of some 3‐F nematicides, this would not account for the inconsistencies observed in this study. Other factors between growing seasons, such as precipitation, soil temperature, cultivar, and microbial activity may have played a more prominent role in contributing to the differences in nematicide performance.…”
Section: Discussioncontrasting
confidence: 57%
“…In experiment 1, all chemical nematicides reduced root galling on tomato, whereas in experiment 2, only fluensulfone showed a trend towards nematode suppression. Although studies have shown that differences in the soil environment, such as organic matter and clay content, can alter nematicidal activity of some 3‐F nematicides, this would not account for the inconsistencies observed in this study. Other factors between growing seasons, such as precipitation, soil temperature, cultivar, and microbial activity may have played a more prominent role in contributing to the differences in nematicide performance.…”
Section: Discussioncontrasting
confidence: 57%
“…pallida , at least during the first 44 DAP, and that population development can also be suppressed. Previous in vitro experiments have indicated that fluensulfone can inhibit nematode hatching and movement. Reducing the size of potential inoculum with respect to the number of J2 that infect a host crop is one, if not the main, principle underlying soil treatments with nematicides, the rationale being the direct relationship between the infection activities of the J2 and crop yield loss .…”
Section: Discussionmentioning
confidence: 97%
“…Wheeler et al (2013) observed the relationship between the irrigation rate, soil moisture and the nematicide performance. The studies of Oka et al (2013) indicated an impact of such soil environments as soil type and organic matter. It is possible that in favorable conditions, the efficacy may increase; however, it requires further detailed studies.…”
Section: Discussionmentioning
confidence: 99%